SELF-ASSESSMENT OF STUDENT YOUTH STATE OF PERSONAL HEALTH AND CHARACTERISTIC OF THEIR APPLICATIONS FOR MEDICAL CARE - Zhdan, V.N.; Slabkyi, H.A.; Zhdanova, O.V. (World of Medicine and Biology, 2019)
The article presents the results of the study on students’ self-estimation of the their personal health status and features of their requests for medical care. During the study, 446 students of various faculties were interviewed. The obtained data analysis indicates that 45 (10.2 ± 1.5%) and 116 (26.0 ± 2.2%) of the students surveyed rated their health as good. The remaining students have chronic diseases. At the same time, 249 (55.8 ± 2.5%) of the respondents have chronic diseases, and 315 (70.6 ± 2.3%) annually fall ill with acute diseases. In the structure of both the morbidity indices and the prevalence of diseases, the first places are occupied by respiratory diseases, digestive diseases and diseases of the musculoskeletal system and connective tissue. There were no statistically reliable differences between the educational departments in terms of health self-estimation. It was found that 316 (70.8 ± 2.3%) students applied to general practitioners, family doctors, for primary care. 317 (71.1 ± 2.3%) students applied for medical help, including 143 (32.1 ± 2.3%) for preventive purposes.
Keywords: students; personal health status; seeking medical care